Progress in the microscopic description of nucleon-nucleus elastic scattering at low-energy - Hao, T. V. Nhan; Tam, Do Quang (Hue University Journal of Science: Natural Science, 2021)
In this brief report, we make a short review of progress in developing the microscopic optical potential in recent years. In particular, we present our current studies and plans on building the microscopic optical potential based on the so-called nuclear structure models at low energies.